An association between polymorphisms within the APOE gene and concussion aetiology in rugby union players. Issue 2 (February 2018) - Abrahams, Shameemah; Mc Fie, Sarah; Patricios, Jon; Suter, Jason; Posthumus, Michael; September, Alison V.
Abstract: Objectives: Concussion refers to changes in neurological function due to biomechanical forces transmitted to the head. The APOE ε4 allele is associated with brain injury severity. The objective was to determine if APOE gene variants are associated with concussion history and severity in rugby players. Design: In total, 128 non-concussed controls and 160 previously concussed participants (all cases N = 160; diagnosed N = 139) were recruited from high school (junior, N = 121), club (N = 116) and professional rugby teams (N = 51). Methods: Participants were genotyped for rs405509 (G > T), rs429358 (T > C) and rs7412 (C > T) APOE variants. Statistical analyses were performed using the R environment. Results: The rs405509 TT genotype was over-represented in controls compared to all cases ( P = 0.043; control: 29%, all cases: 18%; odds ratio: 0.55, 95% confidence interval 0.31–0.98). The APOE -ε isoform frequencies were not significantly different between groups ( P > 0.05). Additionally, the inferred APOE (rs405509-ε2/ε3/ε4) T-ε3 haplotype was over-represented in controls (41%) compared to diagnosed (32%, P = 0.042). The G-ε3 haplotype was under-represented in controls (36%) compared to all cases (44%, P = 0.019) and diagnosed (44%, P = 0.021). The TT genotype was significantly associated with rapid recovery ( P = 0.048, <1 week: 51%, N = 70, ≥1 week: 36%, N = 29; odds ratio: 0.55, 95% confidence interval 0.30–1.01). Conclusions: These findings support the further elucidation of the APOE gene or closely-related genes in concussion aetiology. Although similar preliminary results were found when juniors were separately analysed, the under-powered sample size for junior subgroup requires future investigation in larger cohorts of junior-level athletes.